IMPLEMENTASI METODE SIMULASI DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) KELAS VIII A MTs AL KAUTSAR SRONO TAHUN PELAJARAN 2019/2020 - Ahmad Aziz Fanani; Al Muftiyah (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
This study aims to explain the implementation of the simulation method in learning the history of Islamic culture (SKI) which is applied at MTs Al Kautsar Srono. The background in learning the history of Islamic culture (SKI), where teachers monotonously convey a material in the teaching and learning process, many teachers still use methods that cannot attract the attention of students so that the teaching and learning process in the classroom becomes less conducive. The simulation method is an imitation or action that mimics an event as if it were an actual event. In learning this method emphasizes the fact where students are involved in playing a role in dramatizing the material that has been given. This study aims to describe and analyze the implementation of the simulation method in learning Islamic cultural history (SKI) class VIII A at MTs Al Kautsar Srono for the 2019/2020 academic year. This research is a type of qualitative research by analyzing the results of implementing the simulation method in the learning of Islamic cultural history (SKI) class VIII A MTs Al Kautsar Srono Academic Year 2019/2020. The process of collecting data by researchers used three ways, namely observation, interviews and documentation. For data analysis using descriptive analysis by reducing data, presenting data, then drawing conclusions. Meanwhile, for the validity of the data, the researcher used source triangulation. The results of this study are (1) the learning process of Islamic Cultural History (SKI) class VIII A is carried out in three stages, namely planning, implementing and evaluating. (2) implementation of the simulation method in learning Islamic Cultural History (SKI) Class VIII A students, namely students are able to imitate, present and students are able to ask questions and be able to reflect on the material. (3) the results of class VIII A students in terms of cognitive, affective, and psychomotor are effective.